2014
DOI: 10.1108/ejim-04-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Triple helix going abroad? The case of Danish experiences in China

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:368933 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…These studies, however, still do not explore the adoption of complex and systemic approaches such as the Triple Helix Model (Kwon et al, 2012;Ponds, 2009;Sørensen and Hu, 2014). The EI literature has recognised that successful technological entrepreneurship and internationalisation processes require multiple relationships (i.e., clients, supply chains, governments, and investors) (Fontes and Coombs, 1996;Cooper and Park, 2008;Kim et al, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, however, still do not explore the adoption of complex and systemic approaches such as the Triple Helix Model (Kwon et al, 2012;Ponds, 2009;Sørensen and Hu, 2014). The EI literature has recognised that successful technological entrepreneurship and internationalisation processes require multiple relationships (i.e., clients, supply chains, governments, and investors) (Fontes and Coombs, 1996;Cooper and Park, 2008;Kim et al, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recent research has suggested the emergence of new models of innovation driven by "civil society" called "Quadruple or Quintuple Helix" (Carayannis et al, 2018;Miller et al, 2016;Van Horne and Dutot, 2016;Zhang et al, 2019). Although this would be relevant for the international entrepreneurship literature (Kwon et al, 2012;Sørensen and Hu, 2014), further research should consider the adoption of mixed conceptual frameworks for understanding the determinants/outcomes phenomenon across countries (institutional theory and knowledge spillover theory), as well as considering the final users/consumers (quadruple helix and open innovation).…”
Section: Limitations and Further Directions For Researchmentioning
confidence: 99%
“…Similarly, the branch campus of the Virginia, US, George Mason University in Ras Al Khaimah closed in 2009 after three years of operation. Further, some institutions use direct foreign investment to establish offshore university campuses, which can be considered an expensive approach to internationalizing (Sørensen and Hu, 2014). While the long-term academic and economic outcomes of extant institutions therefore remain to be seen, a critical question raised by the proliferation of foreign university branches in the UAE, given that accreditation is recognition of minimum standards, is why these universities seek beyond accreditation.…”
Section: Internationalization Of He In the Uaementioning
confidence: 99%
“…In the helix model, the government should proactively make necessary adjustments that make the network viable but not have a totalizing role. Thus in such a situation the government should stimulate collaboration through incentive system and should also provide some funding as a mechanize to assure social benefits [49].…”
Section: Literature Reviewmentioning
confidence: 99%